Emergency medical service personnel' post-traumatic stress disorder and psychological detachment: The mediating role of presenteeism - Liao, Dandan; Long, Yanqiong; Yu, Tao; Kang, Xiaoyan; Liu, Shulai; Yan, Jin; Zhang, AiDi (Frontiers in Public Health, 2023)
Background Emergency medical service personnel are subjected to various stressors, which makes them more likely to develop post-traumatic stress disorder symptoms. Studies have shown that psychological detachment and presenteeism play a role at the level of post-traumatic stress disorder. There is no study to examine the relationship between psychological detachment, presenteeism, and post-traumatic stress disorder among emergency medical service personnel. Objective The main objective of the study is to investigate the effects of presenteeism in explaining the relationship between psychological detachment and post-traumatic stress disorder among emergency medical service personnel. Design A cross-sectional study was conducted among 836 emergency medical service personnel in 51 counties and cities in Hunan Province, China. Methods They were anonymously investigated by using the Impact of Event Scale-Revised (IES-R), the Stanford Presenteeism scale-6 (SPS-6), and the Psychological Detachment Scale. Statistic description, univariate analysis, pearson correlation, and structural equation model were adopted to analyze the data. Results The mean score of IES-R, SPS-6, and the psychological detachment scale were 22.44 ± 16.70, 15.13 ± 4.20, and 11.30 ± 4.24. Post-traumatic stress disorder was positively relevant with presenteeism (r = 0.381, p< 0.01), but negatively correlated with psychological detachment (r = −0.220, p < 0.01). And presenteeism partially mediated the association between psychological detachment and post-traumatic stress disorder. Conclusions The results show a high prevalence of post-traumatic stress disorder symptoms in EMS personnel, presenteeism can statistically significantly predict post-traumatic stress disorder symptoms. If hospital management can reduce the presenteeism of emergency medical service personnel, this will help them reduce post-traumatic stress disorder symptoms.